Monetary and financial policy and development policy in MENA countries - (:unkn) unknown (My University, 2018)
The Countries in the Middle East and North Africa are known for their wealth and diversity as a result of a decades-long economic and political history. They extend over a vast expanse from the Persian Gulf to the east, to the Atlantic Ocean to the west. This region sometimes referred to as MENA (Middle East and North Africa) includes most of Southwest Asia and North Africa. It includes on the Asian continent Iran, Turkey and all the Arab countries. In North Africa, it includes Egypt, Tunisia, Libya, Morocco and Algeria.This thesis begins with a first part devoted to the geography and history of the main countries of the region, starting with the last decades lived by the Ottoman Empire.In the second part we present an economic and social panorama of the countries of the zone.In the third part we focus on monetary policy. This policy is one of the most important economic policies, as its success is supposed to contribute to the success and development of other policies. We analyze the problematic relations between the executive government and the central bank as monetary authority.
Keywords: African Research